Using fractional exhaled nitric oxide (FeNO) to diagnose steroid‐responsive disease and guide asthma management in routine care. Issue 1 (7th November 2013) - Price, David; Ryan, Dermot; Burden, Annie; Von Ziegenweidt, Julie; Gould, Shuna; Freeman, Daryl; Gruffydd‐Jones, Kevin; Copland, Anne; Godley, Clifford; Chisholm, Alison; Thomas, Mike
Abstract: Background: Fractional exhaled nitric oxide (FeNO) is a surrogate marker of eosinophilic airway inflammation and good predictor of corticosteroid response. Aim: To evaluate how FeNO is being used to guide primary care asthma management in the United Kingdom (UK) with a view to devising practical algorithms for the use of FeNO in the diagnosis of steroid‐responsive disease and to guide on‐going asthma management. Methods: Eligible patients (n = 678) were those in the Optimum Patient Care Research Database (OPCRD) aged 4–80 years who, at an index date, had their first FeNO assessment via NIOX MINO® or Flex®. Eligible practices were those using FeNO measurement in at least ten patients during the study period. Patients were characterized over a one‐year baseline period immediately before the index date. Outcomes were evaluated in the year immediately following index date for two patient cohorts: (i) those in whom FeNO measurement was being used to identify steroid‐responsive disease and (ii) those in whom FeNO monitoring was being used to guide on‐going asthma management. Outcomes for cohort (i) were incidence of new ICS initiation at, or within the one‐month following, their first FeNO measurement, and ICS dose during the outcome year. Outcomes for cohort (ii) were adherence, change in adherence (from baseline) and ICS dose. Outcomes: In cohort (i) (n = 304) the higher the FeNO category, the higher the percentage of patients that initiated ICS at, or in the one month immediately following, their first FeNO measurement: 82%, 46% and 26% of patients with high, intermediate and low FeNO, respectively. In cohort (ii) (n = 374) high FeNO levels were associated with poorer baseline adherence (p = 0.005) but greater improvement in adherence in the outcome year (p = 0.017). Across both cohorts, patients with high FeNO levels were associated with significantly higher ICS dosing (p < 0.001). Conclusions: In the UK, FeNO is being used in primary practice to guide ICS initiation and dosing decisions and to identify poor ICS adherence. Simple algorithms to guide clinicians in the practical use of FeNO could improved diagnostic accuracy and better tailored asthma regimens.